SimSearch: A new variant of dynamic programming based on distance series for optimal and near-optimal similarity discovery in biological sequences - Deusdado, Sérgio (2009)
http://www.informatik.uni-trier.de/%7Eley/db/conf/iwpacbb/iwpacbb2008.html